2019
DOI: 10.3390/en13010081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Using External Venetian Blinds on the Thermal Comfort of Users of Highly Glazed Office Rooms in a Transition Season of Temperate Climate—Case Study

Abstract: Improving the energy efficiency of buildings is among the most urgent social development tasks due to the scale of energy consumption in this industry. At the same time, it is essential to meet high requirements for indoor environmental quality and thermal comfort. The issue of overheating is most often analysed in summer but it also occurs in transition seasons, when the cooling systems do not operate. The paper attempts to evaluate the effectiveness of external mobile shading elements on the microclimate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For instance, some inaccessible valves that previously were set during construction needed accessibility to permit adjustments, thus, new controls to expand the adjustment ranges had to be added. Yet the biggest impact was the requirement for additional monitoring information of temperatures or intensity of the flowing media as the control system needed to develop predicting capabilities [29].…”
Section: Requirements For Building Automatics Control System (Bacs)mentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, some inaccessible valves that previously were set during construction needed accessibility to permit adjustments, thus, new controls to expand the adjustment ranges had to be added. Yet the biggest impact was the requirement for additional monitoring information of temperatures or intensity of the flowing media as the control system needed to develop predicting capabilities [29].…”
Section: Requirements For Building Automatics Control System (Bacs)mentioning
confidence: 99%
“…The solution presented in the article is a continuation of many years of research, which was the basis for the creation of many articles. In previous studies [25][26][27][28][29][30], the experimental base was discussed in detail along with the possibilities it creates for conducting "in situ" research in the field of automatic process control. The issues concerning the work of individual technical systems (HVAC, lighting, blinds, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The indoor air quality measured with the CO 2 concentration proved to be high in all the buildings. Fedorczak-Cisak et al [34] considered the impact of external shading equipment in office rooms with large glazed areas on indoor thermal comfort. It was observed that the application of external Venetian blinds reduced the ambient air temperatures and the number of discomfort hours by 92%.…”
Section: Introductionmentioning
confidence: 99%